Improvement in Cognition Following Double-Blind Randomized Micronutrient Interventions in the General Population - Denniss, Rebecca J.; Barker, Lynne A.; Day, Catherine J. (Frontiers in Behavioral Neuroscience, 2019)
The impact of poor nutrition on physiological health is well understood (Costarelli, Koretsi, & Georgitsogianni, 2013). Less is known about the effects of diet on brain function and cognition in the general population (Ames, 2010; Parletta, Milte, & Meyer, 2013; White, et al., 2017) and we are still in the early stages of understanding the role of specific nutrients to normal and pathological neuronal functioning. In the present study the putative effect of a multivitamin/mineral or vitamin D supplement on cognitive function over an 8-week period was compared with volunteers taking vitamin C. Healthy adults (N = 60) were recruited, age range 21-59 years (x ̅ = 39.07 years, SD = 11.46), with participants randomly allocated to conditions in a double blind protocol. Participants also completed a 14-day food diary to gather information on micronutrient intake. The cognitive test battery included measures from the WAIS-III (Wechsler, 2008), WMS-IV (Wechsler, 2009) and D-KEFS (Delis, Kaplan and Kramer, 2001), along with the Doors and People (Delis, Kaplan and Kramer, 2001) and a serial reaction time task. Analyses showed better performance on some tasks in all groups following the intervention period, notably on measures of verbal and visual memory and visuomotor processing speed. The Multivitamin group showed significant improvements on tasks of visual strategy generation (along with the Vitamin C group), motor planning, explicit and implicit learning, and working memory. This evidence suggests that sub-optimal micronutrient intake may have a negative effect on cognition across the lifespan.